Technice Numerycznego Rozwiazywania Zagadnień Stateczności Ustrojów Ramowych Hal Przemysłowych - Dowgird, R. (Engineering Transactions, 1963)
The present paper is in close connection with Ref. [1] in which was described an automatic numerical block-Cracovian method for solving stability and redundant problems of a certain class of frame structures now in common use in industrial building. These are structures composed of columns with variable cross-sections elastically clamped in the foundations and connected at any levels by bars or plates on hinged supports attached to the columns. The structures are loaded by any system of transverse and longitudinal forces acting on a column directly on by means of transverse bars or plates (cf. Figs. 2 and 3 of [1] and Figs. 10 and 11 of the present paper). Our aim is to illustrate this method by means of numerical examples and to show its simplicity and usefulness.It is found that it is convenient to introduce the notions of overloaded and underloaded columns corresponding to the notions of active and passive stability used by N. V. KARNAUCHOX, [3], and A. F. SMIRNOV, [4]. These notions are very useful for the design of structures at the stage of profile design.Using digital computions the method purposed in [1] may prove to be very useful.